Prognostic and clinicopathological significance of the Prognostic Nutritional Index in patients with gastrointestinal stromal tumours undergoing surgery: a meta-analysis - Xia Wei; Niansong Kang; Hongping Gu; Yuehan Ni; Sihui Zheng (BMJ Open)
Objectives Previous studies have investigated the prognostic value of the Prognostic Nutritional Index (PNI) in patients with gastrointestinal stromal tumours (GISTs). However, the results have been inconsistent. We performed a meta-analysis to quantitatively determine the prognostic and clinicopathological significance of PNI in GISTs.Design This meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Pooled HRs and 95% CIs were calculated to estimate the prognostic value of PNI in patients with GISTs. Combined ORs and corresponding 95% CIs were used to evaluate the association between the PNI and clinicopathological characteristics.Data sources The electronic databases PubMed, Web of Science, Embase and Cochrane Library were thoroughly searched from inception to December 2021.Eligibility criteria A random-effects model or fixed-effects model was selected based on the level of heterogeneity among the included studies.Results Eight studies comprising 2307 patients were included in this meta-analysis. A low PNI was significantly associated with worse recurrence-free survival (RFS) (HR 2.02, 95% CI 1.66 to 2.47, p<0.001) and overall survival (OS) (HR 4.35, 95% CI 1.25 to 16.83, p=0.033) in patients with GISTs. In addition, a low PNI was significantly associated with tumour size ≥5 cm (OR 1.65, 95% CI 1.21 to 2.24, p=0.002) and primary tumour site in small intestine/colorectum/extra-GISTs (OR 2.03, 95% CI 1.26 to 3.26, p=0.004).Conclusions Patients with GISTs and a lower PNI had inferior RFS and OS. Patients with GISTs and a low PNI may have a higher risk of tumour recurrence.